2009
DOI: 10.1080/00016350902773390
|View full text |Cite
|
Sign up to set email alerts
|

Anterior tooth wear and retention type until 5 years after orthodontic treatment

Abstract: Retention type and, occasionally, an increase in intercanine width influence anterior teeth wear post-treatment. However, the clinical significance and impact of the examined retention methods on occlusal wear are small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
14
0
10
Order By: Relevance
“…There are, however, further concerns that have to be raised in regard to fixed life-long retention. Canines bonded to retainers are reportedly significantly more abraded than un-bonded canines [12], light-cured adhesives bonded to lingual retainers are a source of ongoing bisphenol-A release [7], and since relapse of the anterior alignment is partially due to residual facial growth, permanent retention of incisors and canines will probably not eliminate the issue of crowding, but only shift the problem. Hence, crowding or space creation may occur posterior to the retainer, and compensatory incisor torque may also evolve [24].…”
Section: Life-long Retention (Question 8)mentioning
confidence: 99%
“…There are, however, further concerns that have to be raised in regard to fixed life-long retention. Canines bonded to retainers are reportedly significantly more abraded than un-bonded canines [12], light-cured adhesives bonded to lingual retainers are a source of ongoing bisphenol-A release [7], and since relapse of the anterior alignment is partially due to residual facial growth, permanent retention of incisors and canines will probably not eliminate the issue of crowding, but only shift the problem. Hence, crowding or space creation may occur posterior to the retainer, and compensatory incisor torque may also evolve [24].…”
Section: Life-long Retention (Question 8)mentioning
confidence: 99%
“…A few studies have investigated the tooth wear occurring during the posttreatment period. 4,14 So far, there has been no quantitative report on the tooth wear that occurs during orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigating relationships between tooth wear and previous orthodontic treatment showed no significant effects of horizontal overbite on incisal tooth wear. 19 Silness et al 20 found complex relations between horizontal overbite and increase in incisal wear. Outcomes from studies on the relationship between horizontal overbite and anterior tooth wear therefore remain inconclusive.…”
Section: Discussionmentioning
confidence: 98%